Early Coding Unit–Splitting Termination Algorithm for High Efficiency Video Coding (HEVC). Issue 3 (1st June 2014) - Goswami, Kalyan; Kim, Byung‐Gyu; Jun, Dongsan; Jung, Soon‐Heung; Choi, Jin Soo
Abstract : A new‐generation video coding standard, named High Efficiency Video Coding (HEVC), has recently been developed by JCT‐VC. This new standard provides a significant improvement in picture quality, especially for high‐resolution videos. However, one the most important challenges in HEVC is time complexity. A quadtree‐based structure is created for the encoding and decoding processes and the rate‐distortion (RD) cost is calculated for all possible dimensions of coding units in the quadtree. This provides a high encoding quality, but also causes computational complexity. We focus on a reduction scheme of the computational complexity and propose a new approach that can terminate the quadtree‐based structure early, based on the RD costs of the parent and current levels. Our proposed algorithm is compared with HEVC Test Model version 10.0 software and a previously proposed algorithm. Experimental results show that our algorithm provides a significant time reduction for encoding, with only a small loss in video quality.